2005
DOI: 10.1038/sj.npp.1300673
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Ambient Room Temperature has Differential Effects on MDMA-Induced 5-HT and Dopamine Release in Striatum and Nucleus Accumbens of Rats

Abstract: 3,4-Methylenedioxymethamphetamine (MDMA) produces acute dopamine and 5-HT release in rat brain and a hyperthermic response, which is dependent on the ambient room temperature in which the animal is housed. We examined the effect of ambient room temperature (20 and 301C) on MDMA-induced dopamine and 5-HT efflux in the striatum and shell of nucleus accumbens (NAc) of freely moving rats by using microdialysis. Locomotor activity and rectal temperature were also evaluated. In the NAc, MDMA (2.5 or 5 mg/kg, i.p.) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 51 publications
(50 reference statements)
9
52
0
2
Order By: Relevance
“…Previous studies have shown that the thermoregulatory effects of MDMA depend critically on ambient temperature, with the same doses of MDMA eliciting hypothermia at low ambient temperatures, and hyperthermia at high ambient temperatures (Dafters, 1994;Malberg and Seiden, 1998). Importantly, the locomotor-stimulant effects of MDMA are not affected by ambient temperature (Dafters, 1994;O'Shea et al, 2005). Similarly, the structurally similar synthetic cathinone 4-MMC has recently been shown to exhibit thermoregulatory and locomotor effects distinct from those of MDMA or METH (Wright et al, 2012), suggesting that an evaluation of the role of ambient temperature in MDPV effects is warranted.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have shown that the thermoregulatory effects of MDMA depend critically on ambient temperature, with the same doses of MDMA eliciting hypothermia at low ambient temperatures, and hyperthermia at high ambient temperatures (Dafters, 1994;Malberg and Seiden, 1998). Importantly, the locomotor-stimulant effects of MDMA are not affected by ambient temperature (Dafters, 1994;O'Shea et al, 2005). Similarly, the structurally similar synthetic cathinone 4-MMC has recently been shown to exhibit thermoregulatory and locomotor effects distinct from those of MDMA or METH (Wright et al, 2012), suggesting that an evaluation of the role of ambient temperature in MDPV effects is warranted.…”
Section: Introductionmentioning
confidence: 89%
“…Because ambient temperature has been shown to largely affect the thermoregulatory effects of MDMA (Dafters, 1994;Malberg and Seiden, 1998)-but not to alter locomotorstimulant effects (Dafters, 1994;O'Shea et al, 2005)-we used radiotelemetry to simultaneously monitor both of these end points in response to various doses of MDPV at either 20 or 28 1C. Interestingly, we found that, in contrast to MDMA, locomotor-stimulant effects of 10 mg/kg MDPV were enhanced at the warm ambient temperature.…”
Section: 4-methylenedioxypyrovalerone In Micementioning
confidence: 99%
“…These investigators demonstrated that the increase in the extracellular concentration of DA, as well as 5-HT, in the n. accumbens, but not striatum, is greater at 30° C than at 20°C. On the basis of these results, O'Shea et al (2005) have suggested that the rewarding properties of MDMA may be more pronounced at higher ambient temperatures (O'Shea et al, 2005).…”
Section: Nucleusmentioning
confidence: 98%
“…Finally, O'Shea and coworkers have investigated the influence of ambient temperature on MDMA-induced DA and 5-HT release in the n. accumbens and striatum (O'Shea et al, 2005). These investigators demonstrated that the increase in the extracellular concentration of DA, as well as 5-HT, in the n. accumbens, but not striatum, is greater at 30° C than at 20°C.…”
Section: Nucleusmentioning
confidence: 99%
“…MDMA induces the presynaptic release of dopamine (DA) and serotonin (5-HT) in rats (Gough et al, 1991;Hiramatsu and Cho, 1990;Kankaanpaa et al, 1998;Koch and Galloway, 1997;Schmidt et al, 1987;Yamamoto and Spanos, 1988) and raises extracellular DA and 5-HT in the nucleus accumbens (Nacc) (Kankaanpaa et al, 1998;O'Shea et al, 2005;White et al, 1994), increasing preferentially DA transmission in the shell compared to the core of Nacc (Cadoni et al, 2005). MDMA also produces a stimulatory effect on the release of acetylcholine in the rat prefrontal cortex, striatum, and dorsal hippocampus (Acquas et al, 2001;Nair and Gudelsky, 2006).…”
Section: Introductionmentioning
confidence: 99%